1994
DOI: 10.1901/jeab.1994.61-113
|View full text |Cite
|
Sign up to set email alerts
|

A Contextual Model of Concurrent‐chains Choice

Abstract: An extension of the generalized matching law incorporating context effects on terminal-link sensitivity is proposed as a quantitative model of behavior under concurrent chains. The contextual choice model makes many of the same qualitative predictions as the delay-reduction hypothesis, and assumes that the crucial contextual variable in concurrent chains is the ratio of average times spent, per reinforcement, in the terminal and initial links; this ratio controls differential effectiveness of terminal-link sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
329
6
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(365 citation statements)
references
References 66 publications
28
329
6
2
Order By: Relevance
“…It fits the basic presuppositions of the field: that choice is about response strength, that response strength is equivalent to response probability, and that response rate is a valid proxy for probability (e.g., Skinner 1938Skinner , 1966Skinner , 1986Killeen & Hall 2001). (For typical studies in this tradition see, e.g., Fantino 1981;Grace 1994;Herrnstein 1961Herrnstein , 1964Herrnstein , 1970Rachlin et al 1976; see also Shimp 1969Shimp , 2001 We can also look at concurrent schedules in terms of linear waiting. Although published evidence is skimpy, recent unpublished data (Cerutti & Staddon 2002) show that even on variable-interval schedules (which necessarily always contain a few very short interfood intervals), postfood wait time and changeover time covary with mean interfood time.…”
Section: Concurrent Schedulesmentioning
confidence: 86%
“…It fits the basic presuppositions of the field: that choice is about response strength, that response strength is equivalent to response probability, and that response rate is a valid proxy for probability (e.g., Skinner 1938Skinner , 1966Skinner , 1986Killeen & Hall 2001). (For typical studies in this tradition see, e.g., Fantino 1981;Grace 1994;Herrnstein 1961Herrnstein , 1964Herrnstein , 1970Rachlin et al 1976; see also Shimp 1969Shimp , 2001 We can also look at concurrent schedules in terms of linear waiting. Although published evidence is skimpy, recent unpublished data (Cerutti & Staddon 2002) show that even on variable-interval schedules (which necessarily always contain a few very short interfood intervals), postfood wait time and changeover time covary with mean interfood time.…”
Section: Concurrent Schedulesmentioning
confidence: 86%
“…It should be noted that other interpretations of these approaches are no doubt possible. Additionally, Grace's (1994) contextual choice theory would make predictions comparable to delay reduction in these experiments. The hope was that the results of these experiments would give some sense of the strengths and weaknesses of the three general approaches to risky choice as a function of budget.…”
Section: Of 56 Friday August 15 2003mentioning
confidence: 92%
“…7 DRT loses its quantitative accuracy when applied to schedules other than variableintervals, or to situations in which reinforcer magnitude differs between the two alternatives (but see Grace, 1994). Choice is more extreme than DRT would predict when fixed schedules are used (Duncan & Fantino 1970), and little work has been done examining choice in concurrent chains using ratio schedules (as the studies reported here have done).…”
Section: R E V I E W C O P Ymentioning
confidence: 95%
“…Rachlin (1973) has proposed a non-quantitative theory of contrast similar to the dynamic model sketched out at the end of this chapter. In recent years, Nevin and his associated have elaborated a theory of behavioral "momentum" that can accommodate a wide range of contrast and choice phenomena (e.g., Grace, 1994;Nevin, 1974;Nevin, Tota, Torquato, & Shull, 1990) 12. Use of the term controlled to refer to the effect of a stimulus on a response is conventional, but it is not quite accurate.…”
Section: Theories Of Contrastmentioning
confidence: 99%